Analisa Tingkat Kebisingan Lalulintas di Jalan Raya - Nya Daniaty Malau; Ganti Riang Somasi Manao; Anastasia Kewa (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2017)
Noise is one of the major environmental health problems in big cities. Noise is an unwanted noise that can interfere with and or endanger health. Road traffic is a major source of noise that disrupts most urban communities. The impacts of noise in the housing environment on public health include communication disturbances, psychological disorders, complaints and demonstration actions. The purpose of this research is to know the noise level at Flyover Pasar Rebo and HI Roundabout and to know whether the noise level in Flyover Pasar Rebo and Bundaran HI is still suitable for human hearing. Based on the research that has been done, obtained that the level of kebisisngan in Flyover Pasar Rebo is 62,25 dB. With the highest average noise level of 69 dB which occurred during the day at 11.30-12.00 WIB and at 12:00 to 12:30 pm. While the noise level at Roundabout HI is 61.50 dB. With the highest average noise level of 65 dB which occurred in the morning at 07.30-08.00 WIB. From the data it can be seen that the noise level in Flyover Pasar Rebo is higher than the noise level at Bundaran HI. This is due to the number of vehicles traveling on the highway Flyover Pasar Rebo more than at the HI Round about. Noise levels in the Pasar Rebo and HI Roundabout flyovers are already at